Knowledge on active participation in classroom among nursing and midwifery students - Abebe Abera Tesema; Ebrahim Yimam; Sheka Shemsi (Journal of Education and Learning (EduLearn), 2020)
Effective learning-teaching process is ensured when students interact and actively participate in the learning process. Though most instructors stressed the value of active participation in classrooms of universities and colleges, achieving success in eliciting it appears more difficult. There is high tendency of instructors in higher institutions to cover the tasks and responsibilities of their students. The main aim of this study was to assess the knowledge of and to identify strategies for improving active participation in classroom among nursing and midwifery students. Institution based cross-sectional survey was conducted in Jimma University onrandomlyselected 126 students (81 nursing and 45 midwifery). The collected data were coded, checked and cleaned and entered into SPSS version 23 for analysis. Simple descriptive statistics was used to see the frequency distribution whereas cross-tabulation and Pearson Chi-square test were used to see the association between variables. Majority, 106 (84.1%) of the students had good knowledge about the benefits of active participation in classroom and they suggested strategies to be used by regular classroom teachers to improve students’ participation. Students’ academic year has shown statistically significant association with their knowledge about active participation. The authors of this study strongly recommend instructors to use active learning methods and department heads need to follow teaching methods implemented by their respective faculty.